Relationship Between Pocket Money And Nutritional Status Of Students At SMPN 1 West Karawang - Azzahra, Kayla Ratih; Sefrina, Linda Riski; Elvandari, Milliyantri (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Background: During adolescence, rapid changes occur that affect the nutritional requirements of the foods they eat. Health problems often arise during this period, including nutritional problems that arise during adolescent growth and development. The pocket money teenagers receive can influence how often they choose fast food. The more pocket money they have, the more often they tend to eat fast food because that money is usually used to buy unhealthy foods that are high in fat. Objectives: This research aims to examine the relationship between the amount of pocket money they have and the nutritional status of students at SMPN 1 West Karawang. Research Metodes: This research is a quantitative observational study that uses a cross-sectional approach. The population of this study was class 7J students at SMPN 1 West Karawang. The research sample was taken from the entire population tested using a total sampling technique, which means that all 7J class students at SMPN 1 West Karawang, totaling 37 students, were included in the research. Data analysis was carried out using the Spearman test. Results: In statistical analysis using the Spearman test at a 95% confidence level, a value was obtained (p-value 0.471) for pocket money per day and (p-value 0.186) for pocket money used to buy food and drinks per day. Therefore, with this p-value, the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted. Conclusion: There is no significant relationship between pocket money and the nutritional status of students at SMPN 11 West Karawang. These findings indicate that the pocket money factor has no effect on the nutritional status of adolescents.